Acquisition of analgesic properties by the cholecystokinin (CCK)/CCK2 receptor system within the amygdala in a persistent inflammatory pain condition. Issue 2 (February 2019) - Roca-Lapirot, Olivier; Fossat, Pascal; Ma, Sherie; Egron, Karine; Trigilio, Gabriella; López-González, María-José; Covita, João; Bouali-Benazzouz, Rabia; Favereaux, Alexandre; Gundlach, Andrew L.; Landry, Marc
Abstract : Abstract: Pain is associated with negative emotions such as anxiety, but the underlying neurocircuitry and modulators of the association of pain and anxiety remain unclear. The neuropeptide cholecystokinin (CCK) has both pronociceptive and anxiogenic properties, so we explored the role of CCK in anxiety and nociception in the central amygdala (CeA), a key area in control of emotions and descending pain pathways. Local infusion of CCK into the CeA of control rats increased anxiety, as measured in the light–dark box test, but had no effect on mechanical sensitivity. By contrast, intra-CeA CCK infusion 4 days after Complete Freund's Adjuvant (CFA) injection into the hindpaw resulted in analgesia, but also in loss of its anxiogenic capacity. Inflammatory conditions induced changes in the CeA CCK signaling system with an increase of CCK immunoreactivity and a decrease in CCK1, but not CCK2, receptor mRNA. In CFA rats, patch-clamp experiments revealed that CCK infusion increased CeA neuron excitability. It also partially blocked the discharge of wide dynamic range neurons in the dorsal spinal cord. These effects of CCK on CeA and spinal neurons in CFA rats were mimicked by the specific CCK2 receptor agonist, gastrin. This analgesic effect was likely mediated by identified CeA neurons projecting to the periaqueductal gray matter that express CCK receptors. Together, our data demonstrate that intra-CeA CCK infusion activated a descending CCK2 receptor-dependent pathway that inhibited spinal neuron discharge. Thus, persistent pain induces a functional switch to a newly identified analgesic capacity of CCK in the amygdala, indicating central emotion-related circuit controls pain transmission in spinal cord. Abstract : Supplemental Digital Content is Available in the Text.In inflammatory pain conditions, the CCK/CCK2 system of the central amygdala switches from an anxiogenic to an analgesic role that implicates descending control to the spinal cord.